Marcus Garvey and the vision of Africa (Baltimore, Md. Black Classic Press, 2011)
First published in 1974, and edited by John Henrik Clarke with the aid of Amy Jacques Garvey, this is a superbly edited collection of writings reflecting the life and work of Marcus Garvey. Included are essays by Garvey scholars, contemporaries and critics including Robert Hill, Rupert Lewis, and W.E.B DuBois.
Includes index
Keywords: Africa